Implementasi Sistem Manajemen Transakasi Pemesanan Laundry Sepatu Berbasis Website pada Jivin Clean dengan metode Waterfall - yusuf alvino vino; Sulaibatul Aslamiyah; Tintin Harlina (Sekolah Tinggi Ilmu Komputer PGRI Banyuwangi, 2023)
The purpose of this research is to develop a transaction management system for shoe laundry booking at Jivin Clean, which can assist the owner of Jivin Clean in recording laundry orders. The method used to complete this system is the waterfall method, which consists of several stages, including system requirements analysis, system design, implementation, testing, and maintenance. The outcome of this research is a web-based application for managing shoe laundry booking transactions. In the system, the admin can add and modify order data. Additionally, customers can check the status of their laundry progress. This helps customers know whether their laundry is still in progress or has been completed. The transaction management system for laundry orders at Jivin Clean can assist and facilitate Jivin Clean in recording laundry orders. Furthermore, the system operates efficiently, as evidenced by black-box testing results showing 100% success in testing 15 features.